2023
DOI: 10.1021/acs.est.3c03478
|View full text |Cite
|
Sign up to set email alerts
|

Phytoplankton Biological Pump Controls the Spatiotemporal Bioaccumulation and Trophic Transfer of Antibiotics in a Large Subtropical River

Jinpeng Tang,
Chencheng Zhang,
Yanyan Jia
et al.

Abstract: The spatiotemporal bioaccumulation, trophic transfer of antibiotics, and regulation of the phytoplankton biological pump were quantitatively evaluated in the Pearl River, South China. The occurrence of antibiotics in organisms indicated a significant spatiotemporal trend associated with the life cycle of phytoplankton. Higher temporal bioaccumulation factors (BAFs) were found in phytoplankton at the bloom site, while lower BAFs of antibiotics in organisms could not be explained by phytoplankton biomass dilutio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 78 publications
(222 reference statements)
0
1
0
Order By: Relevance
“…Moreover, a disparity in dominant phytoplankton species was found between the current study and prior studies , and others conducted in deep oligotrophic regions. The Pearl River is a shallow eutrophic river dominated by Cyanophyta, Chlorophyta, and Bacillariophyta. , In those deep oligotrophic and mesotrophic regions, diatoms typically dominate the phytoplankton community. , The results of previous work has indicated that cyanobacteria is the most sensitive group to lincomycin followed by chlorophytes and diatoms . Consequently, exposure to antibiotics often leads to reduced photosynthesis in cyanobacteria, which is considered a common response .…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, a disparity in dominant phytoplankton species was found between the current study and prior studies , and others conducted in deep oligotrophic regions. The Pearl River is a shallow eutrophic river dominated by Cyanophyta, Chlorophyta, and Bacillariophyta. , In those deep oligotrophic and mesotrophic regions, diatoms typically dominate the phytoplankton community. , The results of previous work has indicated that cyanobacteria is the most sensitive group to lincomycin followed by chlorophytes and diatoms . Consequently, exposure to antibiotics often leads to reduced photosynthesis in cyanobacteria, which is considered a common response .…”
Section: Resultsmentioning
confidence: 99%